Найдите корень уравнения: 1) х^2+3х-(1-2х^2)=3х^2-х+4 2) (х-5)^2+(х+4)^2=2х^2

Найдите корень уравнения: 1) х^2+3х-(1-2х^2)=3х^2-х+4 2) (х-5)^2+(х+4)^2=2х^2
Гость
Ответ(ы) на вопрос:
Гость
1. [latex] x^{2} + 3x-(1- 2x^{2}) = 3x^{2} -x+4[/latex] [latex] x^{2} +3x-1+ 2x^{2} - 3x^{2} +x-4=0[/latex] [latex] x^{2} + 2x^{2} - 3x^{2} +3x+x=1-4[/latex] [latex] 4x=-3[/latex] [latex] x=-0,75[/latex] 2. [latex] (x-5)^{2} + (x+4)^{2} = 2x^{2} [/latex] [latex] x^{2} -10x+25+ x^{2} +8x+16- 2x^{2} = 0[/latex] [latex] x^{2} + x^{2} - 2x^{2} -10x+8x=-25+16[/latex] [latex] -10x+8x=-25+16[/latex] [latex]-2x=-9[/latex] [latex]x=4,5[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы